Information Asymmetries and Security Market Design: An Empirical Study of the Secondary Market for U.S. Government Securities - UMLAUF, STEVEN R. (Journal of Finance, 1991)
ABSTRACT This paper examines the empirical implications of an information asymmetry between primary and secondary dealers in the U.S. Government Securities market. This asymmetry arises because primary dealers are permitted to trade through all brokers operating in the marketplace while secondary dealers are restricted to trade through only a subset of brokers. Brokers distribute valuable information over video screens to their trading clients including dealers' up‐to‐date bid‐ask spreads and recent transaction prices. As such, all brokers' video screen information is available to primary dealers, while only a subset of brokers' information is available to secondary dealers. Empirical analyses detect the resulting information asymmetry.